Peculiar Histological Features of Oral Intravascular Papillary Endothelial Hyperplasia - Gabriela Lopes-Santos; Kaique Alberto Preto; Cléverson Teixeira Soares; Denise Tostes Oliveira (SAGE Publishing, 2023)
A 55-year-old male patient with single and well-circumscribed nodule in the lower lip. Accurate diagnosis is based only on histopathological examination using hematoxylin and eosin and immunohistochemical approach, which a large, organized thrombus within the dilated lumen of a poorly demarcated vein, associated with papillary projections of endothelial proliferation occupying vascular spaces. The final diagnosis was intravascular papillary endothelial hyperplasia (IPEH) associated with a thrombus. Oral IPEH is rare and has historically been difficult to diagnose due to its resemblance to other oral lesions. However, the distinctive histological features of oral IPEH associated with a thrombus now allow for its diagnosis through hematoxylin and eosin staining alone, without the need for additional techniques. Therefore, it is crucial for pathologists to be familiar with these unique morphological features to accurately diagnose oral IPEH and differentiate it from more common benign, malignant, or reactive vascular lesions in the oral cavity.